Survey of applications of discrete vortex method in civil engineering. - Nowicki, Tomasz (Budownictwo i Architektura / Civil and Architectural Engineering, 2009)
This paper includes an introduction to Discrete Vortex Method (DVM) and its comparison with other methods of computer fluid dynamics. In its second part it focuses on the most important applications of DVM from the civil engineering point of view. Some examples known form literature are presented theoretical as well as experimental.